Reappraising Effective Regulation in Preventing Human Organs Trafficking in Africa: Kenya and Nigeria in Perspective - Adewumi, Tayewo A.; Ogunkorode, Oluwayemi O. (ABUAD Law Journal, 2022)
Over the years, the issue of illegal human organ harvesting and trafficking has been an international concern. There have been so many stories of victims being promised better opportunies overseas but ended up being untraceable all over the world. The news that most of these people seeking greener pastures abroad must have fallen victim to the illegal international human harvesting and trafficking syndicates is quite alarming. The government of the countries, their citizens to be wary of the "too sweet to be true" job opportunities abroad and a better life abroad. United Nations’ concern on this issue brought about the resolution adopted by the General Assembly at its 73rd session held on 17 December2018 on strengthening and promoting effective measures and international cooperation on organ donation and transplantation to prevent and combat trafficking in person persons for organ removal and trafficking in human organs. This article examines the law relating to organ harvesting and trafficking in Nigeria and Kenya putting into consideration the United Nations resolution. The article observes that Nigeria with its Trafficking in Person (Prohibition) Law Enforcement and Administration Act 2015 and Kenya with the Counter-Trafficking In Persons Act No. 8 of 2010 are yet to adopt the United Nations General Assembly resolution on strengthening and promoting effective measures and international cooperation on organ donation and transplanation to prevent and combat trafficking in persons for organ removal and trafficking in human organs. The article recommends total conformity with theUN resolution.